The Influence of E-Wom on Tiktok Accounts of Brand Tenue De Attire on Brand Awareness - Kunto Ayla Balqiya Vietrandita; Indria Angga Dianita; Chairunnisa Widya Priastuty (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze the influence of Electronic Word of Mouth (e-WOM) on the TikTok platform on the Brand Awareness of the Tenue De Attire brand. The methodology used in this research is a quantitative method with data analysis using SPSS23 software and a survey approach involving 385 active TikTok users who have been exposed to content from the brand through a questionnaire. Based on the study titled “The Influence of e-WOM on the TikTok Account of the Tenue De Attire Brand on Brand Awareness,” a strong relationship and positive influence were found between Electronic Word of Mouth (e-WOM) and Brand Awareness. The correlation coefficient analysis yielded a value of 0.800, indicating a very strong relationship. The R-Square (R²) value of 0.641 indicates that e-WOM explains 64.1% of the variability in Brand Awareness. Simple linear regression results show that each one-unit increase in e-WOM increases Brand Awareness by 0.479. The T-test results show a significance level of 0.000 < 0.05 and a t-value of 26.124 > t-table value of 1.9663, indicating that e-WOM has a significant impact on Brand Awareness.